A Need Analysis for Developing Invertebrate Zoology Practicum Guidelines in Higher Education - Eva Nurul Malahayati; Luthfiya Aqidatu Sholikhah (Indonesian Journal of Biology Education, 2022)
Practical guidelines as learning media in practical activities are needed to facilitate students in an independent study. The purpose of this research is to describe the results of learning media analysis that is needed by students. This research used a qualitative descriptive method. The respondents were 30 students from the Biology Education Study Program, FKIP Balitar Islamic University who had taken the Invertebrate Zoology course. The data analysis technique is to describe the data from the analysis of learning media needs, which are analyzed systematically. The results of this research were 1) students need learning media as guidelines for identifying invertebrate animals in determining species names, 2) learning media that provides material and information through the practical activities presented by the teaching lecturer, 3) Learning media that is easily accessible, presented systematically and uses terms that are easily understood by students.  The results of the analysis are expected to be the basis for developing learning media according to student needs.